2015
DOI: 10.3389/fonc.2015.00232
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging as an Early Biomarker for Radiation Exposure and Microcirculatory Damage

Abstract: BackgroundRadiation exposure can lead to detrimental effects in skin microcirculation. The precise relationship between radiation dose received and its effect on cutaneous perfusion still remains controversial. Previously, we have shown that hyperspectral imaging (HSI) is able to demonstrate long-term reductions in cutaneous perfusion secondary to chronic microvascular injury. This study characterizes the changes in skin microcirculation in response to varying doses of ionizing radiation and investigates these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…RT) and normal tissue applications. With regards to external beam radiation, Chin et al (2012) previously reported spikes on day 1 and 10 in both Hb concentration and StO 2 (as measured by hyperspectral imaging) from beta particle irradiation of mouse skin [17], and Jang et al (2016) confirmed that early cellular changes begin to occur in the first six days post irradiation [26]. These findings agree overall with the trends in our current and previous studies [16].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…RT) and normal tissue applications. With regards to external beam radiation, Chin et al (2012) previously reported spikes on day 1 and 10 in both Hb concentration and StO 2 (as measured by hyperspectral imaging) from beta particle irradiation of mouse skin [17], and Jang et al (2016) confirmed that early cellular changes begin to occur in the first six days post irradiation [26]. These findings agree overall with the trends in our current and previous studies [16].…”
Section: Discussionsupporting
confidence: 83%
“…These findings agree overall with the trends in our current and previous studies [16]. While Chin et al (2015) correlated early trends in optical biomarker parameters with subsequent overall late microvascular damage, differential damage and patterns were due to different administered radiation doses [17]. To our knowledge, we are the first to provide evidence that Hb changes measured on day 1 associate with the severity of radiation induced wounds in connection with treatment intervention.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The utility of NIR spectroscopy and in particular imaging is being explored to determine peripheral vascular perfusion, [121][122][123][124][125] burn injury assessment, [126][127][128][129] as well as the assessment of oxygenation of superficial tissues during surgery, postsurgery, and during healing. [130][131][132][133][134][135][136] Figure 11 shows a tissue oxygenation image derived from a four-wavelength multispectral reflectance image of the planter portion of the foot that has a diabetic ulceration. The ulceration has a very low value of oxygenation compared to the surrounding tissue.…”
Section: Near-infrared Methods To Assess Microvascular Oxygenationmentioning
confidence: 99%